Aplikasi Autoparser Automation Weighting System di PT. Teknologi Flextronics Indonesia - Ryan Binsar Pasaribu; Agung Riyadi (Politeknik Negeri Batam, 2022)
Weighing Automation System is a system that already exists at PT. Flextronics Technology Indonesia. Weighing Automation System is an automatic scale that functions to display the weight of box unit that are complete with components. However, the results of the scales are compared manually by the operator by comparing the results of the weighing scale with the standard range weight on the PC monitor. Based on this, the author created an auto parser application with the aim of producing a desktop application as a component validation system missing in the box unit, and produce a track record of Weighing Automation System. Based on the objectives to be achieved, the problems to be discussed are how to design and build an auto parser application, how to connect the software with the Weighing Automation System and the auto parser application logic to validate the weighing results. This research uses the waterfall method, information gathering, development design, application creation and testing, system installation and maintenance. Through this research, an auto parser application that can be connected to software and a Weighing Automation System with logic can validate the weighing results automatically. With this research, it is expected to reduce human errors during the component validation process in the box unit. The conclusion that the auto parser application can help the validation process for missing components in the box unit